Right to a pain-free end: introducing palliative care learning in Pakistan’s medical education system - Hira Saleem; Muhammad Hassan; Tariq, Muhammad Abdullah (Journal of the Pakistan Medical Association, 2025)
Dear Editor, South Asian countries have a total population of 1.65 billion that makes up more than two-fifths of the developing world’s impoverished population globally. In addition to poverty, healthcare settings in these countries are extremely scarce, leading to delays in diagnosis of progressive ailments such as cancer, thereby increasing the healthcare burden. Additionally, it has been estimated that more than two million people with AIDS reside in these countries. All of the aforementioned statistics make the establishment of adequate palliative care services in South Asia a raging priority1, particularly in Pakistan where less than 1 percent of the population has been estimated to have access to adequate and quality palliative care services.2 Introduction of palliative care education has been deemed pivotal by both internal medicine physicians and surgical residents internationally. A review by Riaz et al. reported that majority of the surgical residency programmed provided limited training of residents in palliative and end of life care, with the situation in Pakistan being ‘alarming’.3 Additionally, a lack of palliative care training of health care professionals, especially in oncology, with the increasing burden of cancer patients, poses a dire need for introduction of courses ranging from the basics of palliative care to specialized training programmes. 2 Furthermore, a cross-sectional study conducted on paediatric residents in Pakistan reported that residents and junior interns felt that a course outlined on management of pain, terminal delirium, and terminal dyspnea would be of extreme benefit to their clinical knowledge and the quality of care imparted.4 The WHO describes the introduction of palliative care via a focus on alterations in medical education curriculum in order to establish a higher standard of care in the long run, alongside other facets, namely availability of medications, and alterations and rigorous implementation in terms of policy drafting.1 A review by Shah et al. makes recommendations on the introduction of palliative care education and services in Pakistan, with direction of special emphasis imparted on offering spiritual care, provision of home nursing services, and education of symptomatic management of cough, nausea, bowel obstruction, and pain.5 The achievement of generalized palliative care services for the population in Pakistan, moreover, requires inter-departmental, intra and inter-communal collaboration among community leaders, government and non governmental organizations, and the general media.2